Solutions of Nonlinear Schrödinger Equation with Two Potential Wells in Linear/Nonlinear Media - Gerasimchuk, V.S.; Gerasimchuk, I.V.; Dranik, N.I. (Журнал математической физики, анализа, геометрии, 2016)
In the framework of nonlinear Schrödinger equation, we analytically studied the nonlinear localized states in the system with two potential holes in the cases of linear and nonlinear media in the holes as well as their linear and nonlinear environment. All the possible solutions for the system are found and studied. The frequency dependences of the field amplitudes for all types of possible stationary localized states are obtained.